Chronic Kidney Disease Increases Risk of Incident HFrEF Following Percutaneous Coronary Intervention - Lai, Wenguang; Zhao, Xiaoli; Yu, Sijia; Mai, Ziling; Zhou, Yang; Huang, Zhidong; Li, Qiang; Huang, Haozhang; Li, Huanqiang; Wei, Haiyan; Guo, Dachuan; Xie, Yun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Chronic kidney disease (CKD) is very common in the percutaneous coronary intervention (PCI) population, who is at high risk of incident heart failure with reduced ejection fraction (HFrEF). However, the harmful effect of CKD on incident HFrEF has not yet been examined among CAD patients undergoing PCI. Methods: Patients undergoing PCI with baseline left ventricular ejection fraction (LVEF) ≥ 40% were included from January 2007 to December 2018 (ClinicalTrials.gov NCT04407936). We defined incident HFrEF as a follow-up LVEF of less than 40% within 3 to 12 months after hospitalization. Multivariable logistical regression was performed to examine the association of CKD with the incident HFrEF. Results: Overall, of 2405 patients (mean age 62.5±10.7 years, 22.3% women), 458 (19.0%) patients had CKD, 86 (3.6%) patients developed incident HFrEF following PCI. The rate of incident HFrEF in the CKD group was higher than in the non-CKD group (7.0% vs 2.8%; p<0.001). Multivariate logistic regression analysis indicated that CKD was an independent risk factor of incident HFrEF [adjusted odds ratio (aOR）=1.71; 95%CI: 1.02-2.84; p=0.038] after adjustment for confounders including age, gender, diabetes, hypertension, congestive heart failure (CHF), baseline LVEF, ACEI/ARB, statins. Furthermore, patients with incident HFrEF have a higher ratio of all-cause mortality compared to those without HFrEF (29.1% vs 10.0%; p<0.001). Conclusions: Our results suggest that CKD is associated with an increased risk of incident HFrEF, which is related to higher all-cause mortality in CAD patients undergoing PCI. On this basis, more aggressive measures for treatment should be taken to prevent the patients with CKD from developing into HFrEF among PCI patients.